Deportations and development: Responding to El Salvador's new migration crisis. (November 2020) - Theodore, Nik
For decades El Salvador has been reliant on migration, mainly to the US, to provide remittances and an outlet for widespread underemployment. The deportation of tens of thousands of migrants annually by the United States, however, threatens to exacerbate problems of joblessness, poverty, and informality in local economies, calling into question the suitability of prevailing economic development strategies. This study proposes an alternative approach—labor force-based development—that was initially proposed to assist US cities confronting widespread job losses following deindustrialization. Through a survey of 198 Salvadorans who were apprehended by US immigration authorities and deported, this article documents deportees' employment experiences in El Salvador and the US, tenure in their primary occupation, education and training obtained, and the localities to which they will return. It also provides recommendations for improving the employment outcomes of deportees. Given that a substantial proportion of deportees have worked in the construction industry, opportunities exist for designing workforce development programs that meet the needs of jobseekers as well as local communities facing housing shortages.